Proses Penghasilan Bromelin daripada Batang Nenas - Wan Daud, Wan Ramli; Yusoff, Mohd. Fauzi; Krishna Rao, D. S (1990)
A proteolytic enzyme called bromelin can be produced from pineapple stem by precipitating it from pineapple stem juice and separating the precipitate from the juice. Acetone is used as the precipitant. The precipitating process is performed twice and the second precipitate is taken as the bromelin product. This process is not well understood and is not amenable to mathematical modelling. The main aim of the present study is to identify process variables such as the precipitant: juice ratio, precipitation time and centrifugation time in every stage which have a significant effect on the yield and activity of bromelin. Factor analysis is used. This study found that the centrifugation times in both stages, precipitation and centrifugation times in the second stage affect the yield of bromelin. The enzyme activity is affected by the precipitant: juice ratio, the precipitation and centrifugation times in the first stage,' precipitant: juice ratio and precipitation time in the second stage. This process is currently being optimised.